2019
DOI: 10.3389/fonc.2019.00098
|View full text |Cite
|
Sign up to set email alerts
|

Trends in and Predictions of Colorectal Cancer Incidence and Mortality in China From 1990 to 2025

Abstract: Colorectal cancer (CRC) has emerged as a major public health concern in China during the last decade. In this study, we investigated the disease burden posed by CRC and analyzed temporal trends in CRC incidence and mortality rates in this country. We collected CRC incidence data from the Cancer Incidence in Five Continents, Volume XI dataset and the age-standardized incidence rate (ASIR) and age-standardized mortality rate (ASMR) of CRC by sex and age, from the 2016 Global Burden of Diseases Study. We used the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
86
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(88 citation statements)
references
References 54 publications
(55 reference statements)
2
86
0
Order By: Relevance
“…Colorectal cancer (CRC) has been identified as one of the most common malignancies, with over 1.8 million new CRC cases and 881,000 deaths estimated in 2018 [1]. With the economic development and changes in lifestyle, a steady increase in CRC incidence was observed in China over the past three decades, revealing an increasing rate from 14.25 per 100,000 in 1990 to 25.27 per 100,000 in 2016 [2]. Family clustering is a typical feature of this disease, with approximately 25% of CRC cases having a first-degree relative (FDR) diagnosed with CRC [3].…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) has been identified as one of the most common malignancies, with over 1.8 million new CRC cases and 881,000 deaths estimated in 2018 [1]. With the economic development and changes in lifestyle, a steady increase in CRC incidence was observed in China over the past three decades, revealing an increasing rate from 14.25 per 100,000 in 1990 to 25.27 per 100,000 in 2016 [2]. Family clustering is a typical feature of this disease, with approximately 25% of CRC cases having a first-degree relative (FDR) diagnosed with CRC [3].…”
Section: Introductionmentioning
confidence: 99%
“…Despite formidable advances in imaging techniques, surgery and multimodal therapy, the overall survival for patients with advanced CRC remains low. A study showed that the incidence of CRC in China has constantly been on the rise over the past three decades and equally predicted a further increase in the near future [2]. According to the 2015 cancer statistics [3], it is estimated that about 2,376,300 new CRC cases and 191,000 CRC related deaths occurred in China, accounting for nearlyone-tenth of the global CRC burden.…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the third most prevalent malignancy in the world. About 274.8 thousand new CRC and 132.1 thousand CRC‐related deaths occurred in China in 2010, and these two numbers are expected to be 624.3 and 221.1 thousand by 2025 . Currently, tumor node metastasis (TNM) stage is the most important prognostic factor.…”
Section: Introductionmentioning
confidence: 99%